Diseño de un sistema para la obtención de agua limpia mediante la aplicación de energías alternativas en el Campus Ceypsa. - Tigasi Tigasi, Carlos Javier (2017)
The general consumption of bottled water by the university community on the CEYPSA campus has caused problems such as the high cost of water, increased risk to health by existing chemicals in plastics (disphenyl A-B) and above all the increase in solid waste generation. It was proposed to design a prototype of a parabolic solar concentrator. It consists of evaporation systems to raise the water temperature and condensation system for the cooling of the water vapour. The aim was to design a sustainable and low environmental impact system on the CEYPSA campus, to obtain clean, safe and environmentally friendly water through the application of alternative energies such as solar and wind energy. We analyzed the data of the meteorological station of the campus (CEYPSA), in order to know the climatic variations of heliophany and the speed of the wind. This system was designed for a water adequacy process, raising water temperature above 100 ° C in order to eliminate pathogenic microorganisms. The solar energy potential that concentrates on the prototype that is of 4766, 23Kcal and the wind potential that is of 1.79 m/s. Under these physical conditions will be generated 56 liters daily of clean and safe water for the wellbeing of the university community. To verify the quality of the water, a previous pre-analysis of the sector was carried out in which the mesophiles and Colibacilos total aerobics do not meet the permissible ranges compared with the standard Inen 1108. Finally, a later analysis was carried out in which the parameters mentioned above by the increase of the temperature above 100 ºC are died because their maximum limits of survival is 30 – 40 ºc, therefore they are within the permissible ranges and are considered suitable for human consumption. Key words: Alternative energies, prototype, climatic variations and water quality.